2020
DOI: 10.1155/2020/3890706
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Direct-Acting Oral Anticoagulants (DOACs) in the Overweight and Obese

Abstract: Obesity plays an essential role in the safety of pharmacologic drugs. There is paucity of data for direct oral anticoagulants (DOACs) in the obese, despite these agents becoming more widely used. The primary and secondary objectives of this study were to assess the safety and efficacy of DOACs in the overweight and obese populations when used for primary prophylaxis in the setting of non-valvular atrial fibrillation (NVAF) and for treatment of venous thromboembolisms (VTE). We conducted a retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The other available data on obese patients are based on post hoc analyses of randomized trials, registries, retrospective studies or healthcare claims databases. These studies showed minor effects of obesity on DOAC PK and reported similar efficacy and safety of DOACs across the different weight groups, and versus vitamin K antagonists, suggesting DOAC efficacy and safety in obese patients [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The other available data on obese patients are based on post hoc analyses of randomized trials, registries, retrospective studies or healthcare claims databases. These studies showed minor effects of obesity on DOAC PK and reported similar efficacy and safety of DOACs across the different weight groups, and versus vitamin K antagonists, suggesting DOAC efficacy and safety in obese patients [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some of these studies had incomplete adjustment for confounding factors at baseline and the others were limited by small sample size and retrospective nature of the analyses. Higher BMI and waist circumference were associated with a favourable prognosis (adjusting for comorbidities and treatment allocation) in patients treated with oral anticoagulants [31,32]. In an analysis of patients treated with edoxaban and warfarin included in the ENGAGE AF-TIMI 48 trial, higher BMI (per 5 kg/m 2 increase) was independently associated with lower risks of stroke/SEE and death, but with increased risk of major bleeding.…”
Section: Discussionmentioning
confidence: 98%
“…More investigation should be done debating whether warfarin or NVKAs are the better choice for high risk VTE patients. According to the linked studies, DOACs remain to be the preferable choice regardless, due to their rapid onset of action, standard dosages without the need of titration, lack of requirement of routine check-ups, and limited interactions with food and associated drugs [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] ].…”
Section: Discussionmentioning
confidence: 99%